Effect of introduction of integrated out of hours care in England: observational study. Issue 7508 (7th July 2005) - Lattimer, Val; Turnbull, Joanne; Burgess, Abigail; Surridge, Heidi; Gerard, Karen; Lathlean, Judith; Smith, Helen; George, Steve
Abstract: Objectives To quantify service integration achieved in the national exemplar programme for single call access to out of hours care through NHS Direct, and its effect on the wider health system. Design Observational before and after study of demand, activity, and trends in the use of other health services. Participants 34 general practice cooperatives with NHS Direct partners (exemplars): four were case exemplars; 10 control cooperatives. Setting England. Main outcome measures Extent of integration; changes in demand, activity, and trends in emergency ambulance transports; attendances at emergency departments, minor injuries units, and NHS walk-in centres; and emergency admissions to hospital in the first year. Results Of 31 distinct exemplars, 21 (68%) integrated all out of hours call management. Nine (29%) achieved single call access for all patients. In the only case exemplar where direct comparison was possible, a higher proportion of telephone calls were handled by cooperative nurses before integration than by NHS Direct afterwards (2622/6687 (39%) v 2092/7086 (30%): P < 0.0001). Other case exemplars did not achieve 30%. A small but significant downturn in overall demand for care seen in two case exemplars was also seen in the control cooperatives. The number of emergency ambulance transports increased in three of the four case exemplars after integration, reaching statistical significance in two (5%, −0.02% to 10%, P = 0.06; 6%, 1% to 12%, P = 0.02; 7%, 3% to 12%, P = 0.001). This was always accompanied by a significant reduction in the number of calls to the integrated service. Conclusion Most exemplars achieved integration of call management but not single call access for patients. Most patients made at least two telephone calls to contact NHS Direct, and then waited for a nurse to call back. Evidence for transfer of demand from case exemplars to 999 ambulance services may be amenable to change, but NHS Direct may not have sufficient capacity to support national implementation of the programme.